2013
DOI: 10.1103/physrevb.87.064401
|View full text |Cite
|
Sign up to set email alerts
|

Common effect of chemical and external pressures on the magnetic properties ofRCoPO (R=La, Pr)

Abstract: We report a detailed investigation of RECoPO (RE = La, Pr) and LaCoAsO materials performed by means of muon spin spectroscopy. Zero-field measurements show that the electrons localized on the Pr 3+ ions do not play any role in the static magnetic properties of the compounds. Magnetism at the local level is indeed fully dominated by the weakly-itinerant ferromagnetism from the Co sublattice only. The increase of the chemical pressure triggered by the different ionic radii of La 3+and Pr 3+ , on the other hand, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 60 publications
3
71
1
Order By: Relevance
“…Indeed, recently it has been argued that electronic inhomogeneity controlled by organization of defects, lattice distortions, interface states, nanoscale phase separation in the layered oxides has substantial influence in the superconducting properties of cuprates [4][5][6][7][8][9]. This appears to be common to all layered superconductors as diborides [10][11][12][13] and more recently pnictides [14][15][16][17][18][19]. Here it should be specified that large structural differences from one cuprate family to another one hinders the investigation of what drives the T c max in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recently it has been argued that electronic inhomogeneity controlled by organization of defects, lattice distortions, interface states, nanoscale phase separation in the layered oxides has substantial influence in the superconducting properties of cuprates [4][5][6][7][8][9]. This appears to be common to all layered superconductors as diborides [10][11][12][13] and more recently pnictides [14][15][16][17][18][19]. Here it should be specified that large structural differences from one cuprate family to another one hinders the investigation of what drives the T c max in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…14 7 14 and PrFeAsO 12, 16 one wonders how different will be the situation for PrCoAsO. Very recently some of us reported 17,18 the muon spin spectroscopy and nuclear magnetic resonance (NMR) on RECoPO (RE = La, Pr) and found that Co exhibit weak itinerant FM for both La and Pr. This prompted us to study in detail the magnetic and magneto-transport properties of our PrCoAsO samples and compare the same with reported data on (La,Nd,Sm,Gd)CoAsO.…”
Section: Introductionmentioning
confidence: 99%
“…µ + SR data analysis was performed similarly to what discussed in Ref. 27, and the same notation will be employed in the current paper for the aim of clearness. In particular, the general expression…”
Section: 3940mentioning
confidence: 99%
“…25,26 At the same time, we have previously shown that the Co-based ferromagnetic (FM) compounds RCoPO are an ideal playground to investigate the interplay of chemical and external pressures. 27 There, we reported by means of muon-spin spectroscopy (µ + SR) and density-functional theory (DFT) calculations that ferromagnetism is sizeably enhanced with increasing P for both LaCoPO and PrCoPO. 27 In this paper, we extend our previous investigation to the case of NdCoPO and SmCoPO.…”
mentioning
confidence: 99%
See 1 more Smart Citation